Prevalence of MRSA Nasal Carriage in Patients Admitted to a Tertiary Care Hospital in Southern India - George, Kalpana (J Clin Diagn Res, 2016)
INTRODUCTION: Infections with MRSA, both community and hospital acquired, are well established and the source of infection is often a carrier. There are very few studies showing the magnitude of MRSA nasal colonization among healthy persons from the community. This study was conducted to detect the prevalence of MRSA nasal carriage in patients who did not have any known risk factors associated with HA- MRSA colonization, admitted to a tertiary care centre in Kerala. MATERIALS AND METHODS: Nasal swabs were collected from patients within 24 hours of admission. Specimen were inoculated on chromogenic agar (HiCrome MeReSa agar-HiMedia) for MRSA screening. Isolates were then subjected to antibiotic sensitivity tests, SCCmec typing and PVL gene detection. RESULTS: Out of 683 patients, 16 carried MRSA in their nares (2.3%). Of the 16 strains 13 (81.25 %) strain were SCCmec type III and one belonged to SCCmec type IV (6.25 %). Two strains failed to amplify SCCmec genes. Three strains carried genes for PVL toxin (18.75%). CONCLUSION: With a better understanding of the complex epidemiology of MRSA it is increasingly apparent that demarcations between the HA and CA phenotypes are not as clear cut as previously thought. In this study of nasal carriage of MRSA in the community we have demonstrated prevalence consistent with published data. Most isolates however were shown to belong to the type conventionally assigned to HA-MRSA.